2021
DOI: 10.1051/0004-6361/202039633
|View full text |Cite
|
Sign up to set email alerts
|

The Fornax Deep Survey (FDS) with the VST

Abstract: Context. Galaxies either live in a cluster, a group, or in a field environment. In the hierarchical framework, the group environment bridges the field to the cluster environment, as field galaxies form groups before aggregating into clusters. In principle, environmental mechanisms, such as galaxy–galaxy interactions, can be more efficient in groups than in clusters due to lower velocity dispersion, which lead to changes in the properties of galaxies. This change in properties for group galaxies before entering… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 126 publications
2
69
0
Order By: Relevance
“…• Background galaxies: Small galaxies that show features like spiral arms or bars. These properties are not likely to appear in low-mass dwarfs (Janz et al 2014;Su et al 2021), thus we conclude that they are background galaxies. We are aware that some massive dwarf galaxies can show prominent disk-like features, with star forming regions, resembling spiral galaxies (Lisker et al 2006;Michea et al 2021).…”
Section: Visual Classificationmentioning
confidence: 72%
See 1 more Smart Citation
“…• Background galaxies: Small galaxies that show features like spiral arms or bars. These properties are not likely to appear in low-mass dwarfs (Janz et al 2014;Su et al 2021), thus we conclude that they are background galaxies. We are aware that some massive dwarf galaxies can show prominent disk-like features, with star forming regions, resembling spiral galaxies (Lisker et al 2006;Michea et al 2021).…”
Section: Visual Classificationmentioning
confidence: 72%
“…The set of the former processes is usually called mass quenching because they are all related to the mass of the galaxy. These internal mechanisms usually affect mostly massive early-type galaxies (Su et al 2021). Studies focused on isolated early-type galaxies, for which external influences can be excluded, have shown that mass quenching is effective only for galaxies more massive than 10 9 M (Geha et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For each oriented snapshot we fed its surface brightness map to statmorph (Rodriguez-Gomez et al 2019) isolating the region of the map within 27 mag/arcsec 2 . As a reference, Su et al (2021) find an Asymmetry of 0.23 for NGC 1427A. We tried to add the Asymmetry to the constraints described in Section 4.1.…”
Section: Including Asymmetry As a Constraintmentioning
confidence: 99%
“…However, recent studies suggest they are not as simple as once thought. Most cluster dwarf ETGs are not well fit by a single Sérsic profile and often contain additional structures such as bars and lenses (Janz et al 2012, Su et al 2021). Nuclei are a common feature, especially in more massive dwarf ETGs (Lotz et al 2004;Côté et al 2006;Paudel et al 2010Paudel et al , 2011Neumayer et al 2020).…”
Section: Introductionmentioning
confidence: 99%